System zarządzania jakością a skuteczność funkcjonowania administracji publicznej na przykładzie Urzędu Miasta Nowego Sącza - Kalisz, Jerzy (My University, 2013)
Zakres pracy dotyczy problematyki związanej z wprowadzeniem w organach administracji publicznej Systemu Zarządzania Jakością. Celem pracy jest pokazanie wpływu wdrożenia Systemu Zarządzania Jakością na skuteczność funkcjonowania urzędu. Wprowadzony w Urzędzie Miasta Nowego Sącza System Zarządzania Jakością według normy ISO 9001:2008 poddano szczególnym badaniom. W tym celu wykorzystano analizę dokumentów urzędu i badania ankietowe. W badaniach podjęto próbę odpowiedzi na pytanie, czy posiadanie normy ISO 9001:2008 zwiększyło satysfakcję odbiorców oraz usprawniło pracę urzędu.

This thesis focuses on issues related with the introduction of the Quality Management System into the public administration. The aim of this study is to show the impact of implementation of the Quality Management System on the effective functioning of the office. Introduced into the office of the NowySącz City Council, Quality Management System according to ISO 9001:2008 was carefully and thoroughly tested. This process included the analysis of the office documents and survey results. This thesis is an attempt to answer the question whether having ISO standard 9001:2008 increases satisfaction of the customers and makes the office work more efficient.
Quality Management System and effectiveness of functioning of public administration; case study: administrative office of Nowy Sącz City Council
Keywords: zarządzanie jakością; urząd; certyfikat ISO; quality management; office; ISO certificate